2011
DOI: 10.5402/2011/279607
|View full text |Cite
|
Sign up to set email alerts
|

The Predictivity of Serum Biochemical Markers in Acute Biliary Pancreatitis

Abstract: Background and Aim. There are no accurate methods of differentiating acute biliary pancreatitis. Obstructions of biliary ducts, idiopathic pancreatitis may be related with biliary origin which needs identification for acute treatment. We searched for the predictivity of biochemical markers in early acute biliary pancreatitis. Patients and Methods. Serum levels of AST (Aspartate Transaminase),ALT (Alanine Transaminase), ALP (Alkaline Phosphatase), GGT (Gamma Glutamyl Transferase), total bilirubin, direct biliru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 22 publications
1
33
1
Order By: Relevance
“…30 In addition to PEP, overall complications of ERCP were 1.52times higher in women. 29 In contrast, there was no significant association between age or sex and PEP in our study, even slightly higher risk of PEP, but not significant, was observed. Interestingly, lack of association between age and sex and the risk of PEP also has been observed by Cheng et al 31 In the searching for patient-related risk factors, previous evidences has reported that post-ERCP elevation of inflammatory and biochemical markers could be a potential predictors of PEP.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…30 In addition to PEP, overall complications of ERCP were 1.52times higher in women. 29 In contrast, there was no significant association between age or sex and PEP in our study, even slightly higher risk of PEP, but not significant, was observed. Interestingly, lack of association between age and sex and the risk of PEP also has been observed by Cheng et al 31 In the searching for patient-related risk factors, previous evidences has reported that post-ERCP elevation of inflammatory and biochemical markers could be a potential predictors of PEP.…”
Section: Discussioncontrasting
confidence: 87%
“…In relation to patient-related risk factors, previous studies have discussed that being female and younger ages were significant risk factors for PEP. 29 The impact of age seems to be related to protective effect of progressive decline in pancreatic exocrine function by aging. 30 In addition to PEP, overall complications of ERCP were 1.52times higher in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, in idiopathic AP, we defined the elevation of serum alkaline phosphatase (ALP) and increased alanine aminotransferase (ALT) (≥3 times the upper limit of normal) as findings suggestive of microlithiasis. [16][17][18][19][20] …”
Section: Definitionmentioning
confidence: 99%
“…27,28 Several studies have shown that elevated ALP is a common marker for diagnosing gallstone-induced pancreatitis. 16,18 Several recent reports proposed that the ALT level might be a marker for early recognition of a gallstone etiology in patients with AP. 17,19,20,29 In particular, increased ALT, ≥3-fold the normal level, highly suggests microlithiasis.…”
Section: 2412mentioning
confidence: 99%